Determining standard of academic potential based on the Indonesian Scholastic Aptitude Test (TBS) benchmark - Idwin Irma Krisna; Djemari Mardapi; Saifuddin Azwar (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2016)
The aim of this article was to classify The Indonesian Scholastic Aptitude Test or Tes Bakat Skolastik (TBS) results for each subtest and describe scholastic aptitudes in each subtest. The subject of this study was 36,125 prospective students who took the selection test in some universities. Data analysis began by estimating testees’ ability using the Item Response Theory, and benchmarking process using the scale anchoring method applying ASP.net web server technology. The results of this research are four benchmarks (based on cutoff scores) on each subtest, characters which differentiate potential for each benchmark, and measurement error on each benchmark. The items netted give a description of the scholastic aptitude potential clearly and indicate uniqueness so that it could distinguish difference in potential between a lower bench and a higher bench. At a higher bench, a higher level of reasoning power is required in analyzing and processing needed information so that the individual concerned could do the problem solving with the right solution. The items netted at a lower bench in the three subtests tend to be few so that the error of measurement at such a bench still tends to be higher compared to that at a higher bench.